Evolution of differential maternal age effects on male and female offspring development and longevity. (9th July 2014) - Lind, Martin I.; Berg, Elena C.; Alavioon, Ghazal; Maklakov, Alexei A.
Summary: Maternal age effects on life‐history traits, including longevity, are widespread and can be seen as a manifestation of ageing. However, little is known about how maternal life span may influence the maternal age effect. At a given chronological age, a long‐lived parent may be at a younger biological age than a short‐lived parent and thus has a less severe parental age effect. However, earlier work using experimentally evolved short‐ and long‐lived lines did not support this hypothesis. We scored developmental time and longevity of 14 995 individual seed beetles, Callosobruchus maculatus derived from replicate short‐lived and long‐lived lines created via artificial selection on male life span. Offspring from older mothers had shorter life span, which is consistent with most of the literature. We found support for the hypothesis that detrimental maternal age effects evolve to be weaker under selection for long life span. However, this finding was only apparent in males, suggesting that maternal age affects male and female offspring differently. These results suggest that sex‐dependent parental age effects should be incorporated in the studies of longevity and ageing evolution and that selection on one sex can cause evolution of parental age effects in the other sex. Abstract : Lay Summary